2017
DOI: 10.1158/1538-7445.am2017-524
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 524: Characterizing the in vitro and in vivo effects of the PIM kinase inhibitor HS140 in triple-negative human breast cancer

Abstract: Triple-negative breast cancer (TNBC) lacks expression of the estrogen receptor (ER), the progesterone receptor (PR) and the ERBB2 (also known as HER2) receptor, making it the worse subtype of all breast cancers. Currently, there are no molecular targeted therapies for this cancer and chemotherapy is only successful in a limited number of patients. Recent studies suggest that members of the oncogenic PIM kinase family, especially PIM-1, play a significant role in the growth of TNBC. However, there is very limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…1). This has already been described by Brasó-Maristany et al and others who identified increased PIM 1 expression in TNBC that correlated with increased proliferation and protection from apoptosis [12,51].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…1). This has already been described by Brasó-Maristany et al and others who identified increased PIM 1 expression in TNBC that correlated with increased proliferation and protection from apoptosis [12,51].…”
Section: Discussionsupporting
confidence: 74%
“…Overall, considering the encouraging evidence surrounding PIM kinase inhibitors in combination with other inhibitors in cancer therapy [31,32,63], and evidence suggesting targeting multiple pathways simultaneously will rescue sensitivity [18,20,22,51], as well as the in vitro and in vivo studies of IBL-302 in preclinical breast cancer models presented in this paper, we believe that the dual PI3K/mTOR and PIM inhibitor IBL-302 should be investigated further in breast cancer. We thus plan, to take the compound to phase I clinical trial evaluation in heavily pretreated breast cancer patients.…”
Section: Discussionmentioning
confidence: 89%